Investigating the Structural Relationships of the Tendency to Addiction to Mobile Phone-Based Social Networks in Students, Based on Early Maladaptive Schemas Mediated by Alexithymia in Students - Pouria Moghimy; Forough Esrafilian; Hojjatollah Farahani (پژوهش‌های کاربردی روانشناختی)
The aim of current research was to investigating structural relationships of addiction to mobile phone-based social networks in students, as influenced by early maladaptive schemas mediated by alexithymia. In terms of purpose, this research was applied research, while in terms of method, it was correlational studies. The statistical population of this survey comprised all individuals between the ages of 18 and 30 who resided in Tehran and Isfahan in 2021. The available sampling method was employed to select a sample of 524 individuals, which included 381 girls and 143 boys. Mobile Social Network Addiction (SNA), Toronto Alexithymia (TAS_20), and the Young Schema Questionnaire-Short Form3 (YSQ-S3) were completed by the participants. The research data was analyzed using structural equation modeling and the R-4.2 and SPSS-26 software. Based on research findings, variable of maladaptive schemas was able to predict the tendency to addiction to social networks in a positive and significant manner. However, there was no significant relationship between Alexithymia and the propensity to develop an addiction to social media. Results showed that Alexithymia does not play a mediating role in predicting tendency to addiction to social networks based on maladaptive schemas. It is recommended that psychologists and counselors consider the role of early maladaptive schemas in the prevention, control, and treatment of addiction to social networks in light of the results obtained.